2017
DOI: 10.17559/tv-20151027225413
|View full text |Cite
|
Sign up to set email alerts
|

New stress-strain model for concrete at high temperatures

Abstract: Original scientific paper Concrete is one of the most widely used materials in civil engineering structures. Extremely high temperatures can seriously damage the concrete structure, leading to degradation of its mechanical properties. Considering high temperatures in civil engineering applications is strongly connected with the fire scenarios in which temperatures in concrete can reach 1000 °C. For using computer software for analysis of the reinforced concrete structures, it is essential to formulate constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…In this work, an analytical model is theoretically substantiated, which coincides with the experimentally substantiated Furamura model [17] known from the literature (an analysis of the Furamura model is also available in [14,18]). In addition to the data known from the literature, the model was analyzed using definitions known in fracture mechanics, such as damage function, effective area, effective stresses, and effective elastic modulus.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…In this work, an analytical model is theoretically substantiated, which coincides with the experimentally substantiated Furamura model [17] known from the literature (an analysis of the Furamura model is also available in [14,18]). In addition to the data known from the literature, the model was analyzed using definitions known in fracture mechanics, such as damage function, effective area, effective stresses, and effective elastic modulus.…”
Section: Introductionmentioning
confidence: 57%
“…However, effective In this study, the application of the basic concepts of fracture mechanics to the substantiation of the total stress-strain relations for concrete under uniaxial compression is considered. Such relationships have been studied in numerous works, reviews of which can be found in the articles [12][13][14]. However, an analysis of the literature showed that the following questions that determine the purpose of this work remained insufficiently studied: How does one explain that concrete samples under uniaxial compression fail on the descending branch of the stress-strain diagram?…”
Section: Mechanical Model: a Brief Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be assumed that the model ( 1)-( 18) is too simple to analyze such a complex object as a trabecular tissue, for which some transformation of the structure is possible [40,41] and changes in the interaction of structural elements during tension. The use of models with parameters [35,42] may be promising both for improving the results of the analysis and for expanding the scope of such models [43]. As can be seen, the model (16a) adequately reflects the trends of growth crease of apparent stresses at the stages before and after the point of the stress ex (Figure 10).…”
Section: Discussionmentioning
confidence: 97%
“…It can be assumed that the model ( 1)-(1 simple to analyze such a complex object as a trabecular tissue, for which some t mation of the structure is possible [40,41] and changes in the interaction of structu ments during tension. The use of models with parameters [35,42] may be promisi for improving the results of the analysis and for expanding the scope of such mode Nevertheless, for compression, quite adequate results were obtained us model ( 1)-(18) (Figures 3, 4, and 6-12). In addition, using the energy criterion in t (3) and the ideas of fracture mechanics [23,24], the following are justified: the resource function (6) and the damage function (7); the formulas for determining fective elastic modulus using experimental data (8), (10), (11), and the apparent m of elasticity (14); the functions of load-displacement (15a) and of apparent stres (16a); and the hypothesis about the consolidation of the particles of the destroyed at the final stage of compression tests (Section 3.4).…”
Section: Discussionmentioning
confidence: 99%